DESIGNING THE ACCOUNTING INFORMATION SYSTEM OF CASH RECEIPT AND CASH DISBURSEMENT (CASE STUDY IN PT. INCORE KARYA UTAMA) - Michelle, Michelle (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2020)
The study is aims to design the accounting information system of cash receipt systems and cash disbursement systems in PT. Incore Karya Utama. The author will also give the best practice of accounting information system for PT. Incore Karya Utama, especially in cash receipt systems and cash disbursement systems. It is expected can help the company to organize the cash neatly which is affected in maintaining the company?s wealth. The current study uses the qualitative methodology in the case study research design and the used type of data is the secondary data. The data is collected using 3 methods, such as interview, documentation, and observation. The author is used the Miles and Huberman model as the analysis data technique which contains 3 steps, such as data reduction, data display, and verification. After that, the data is analyzed using 2 step, such as data processing and system design. The result of the research are there are some weaknesses in the accounting information system of cash receipt and cash disbursement of PT. Incore Karya Utama, such as there is no function separation between the managing of cash-in and cash-out with the receipt or disburse of physical money and the financial statement made by the accounting staff is not examined by the financial director. The recommendation of AIS for PT. Incore Karya Utama have been made. It is proper and fit with the company situation. It is expected that PT. Incore Karya Utama can used those recommendations, so that the company can run well its business activities.Keyword: Accounting Informations Systems, Cash Receipts, Cash DisbursementREFERENCES Anonymous. (2017, November 20). Dipetik November 4, 2019, dari https://www.situstekniksipil.com/2017/11/definisi-kontraktor.htmlBahri, S. E., M. S. A., S. (2016). Pengantar Akuntansi. Yogyakarta: CV. ANDI OFFSET.Baridwan, M.Sc., Akuntan, D. (2002). Sistem Informasi Akuntansi. Yogyakarta: BPFE.Bodnar, G., & Hopwood, W. (2010). Accounting Information System. 10th Edition. United State of America: Pearson Education Inc.Erika. (2010). Laporan Prakter Kerja Lapangan tentang Sistem Akuntansi Penerimaan dan Pengeluaran Kas pada PT. Yepupe Perise Ramadhani Pekanbaru.Esteria, N. W., Sabijono, H., & Lambey, L. (2016). Analisis Sistem Akuntansi Penerimaan dan Pengeluaran Kas pada PT. Hasjrat Abadi Manado. Jurnal Berkala Ilmiah Efisiensi, 16 No.4.Fahmi, M. I., Kertahadi, & Azizah, D. F. (2015). Analisis Sistem Akuntansi Penerimaan dan Pengeluaran Kas Guna Mendukung Pengendalian Intern Perusahaan (Studi pada PT. Tambora Mulyorejo Malang Jawa Timur). Jurnal Administrasi Bisnis, 26 No.2.Hall, J. (2010). Accounting Information Systems. United Stated of America: Cengage Learning.Halman, S. U. (2014, September 10). Dipetik October 7, 2019, dari http://utamitamii.blogspot.com/2014/10/analisis-data-kualitatif-model-miles.htmlHery, S. (2015). Pengantar Akuntansi. Jakarta: Grasindo.Kieso, D., Jerry, W., & Terry, W. (2014). Intermediate Accounting (2 ed.). USA: Wiley.McLeod, R., & Shell, G. (2006). Management Information System (10th ed.). Prentice Hall.Moscove, S., & Simkin, M. (1981). Accounting Information System Concepts and Practice for Effective Decision Making. New York: John Wiley and Sons, Inc.Mukjizatiah, S., & Arisman, A. (2017). Analisis Sistem Informasi Akuntansi Penerimaan dan Pengeluaran Kas pada PT. Mardiatama Konstruksi Palembang.Mulyadi. (2001). Sistem Akuntansi. Jakarta: Penerbit Salemba Empat.Murdick, et al, R. (1978). Accounting Information System. Englewood Cliffs N. J.: Prentice Hall, Inc.Mursyidi. (2010). Sistem Akuntansi. Bogor: Ghalia Indonesia.Nisa, K. (2017). Analisis dan Perancangan Sistem Informasi Akuntansi Penerimaan dan Pengeluaran Kas PT. Adiyasa Cipta Gemilang.Nur, M. (2013). Analisis Sistem Akuntansi Penjualan pada PT. Tiga Berlian Sejahtera.O'Brien, J., & Marakas, G. (2011). Management Information System (10th ed.). McGraw-Hill Education.Pranandari, R. P. (2017). Perancangan Sistem Akuntansi Penerimaan Kas pada Usaha Cucian Mobil